2021
DOI: 10.1371/journal.pone.0245953
|View full text |Cite
|
Sign up to set email alerts
|

Tourist willingness to pay for local green hotel certification

Abstract: This study aims to understand tourists’ willingness to pay a price premium for a local green hotel certification, and is one of only a few in the literature for small-island tourism destinations in emerging economies with their unique and pressing sustainability challenges. In a survey of 535 tourists visiting Gili Trawangan, Indonesia, facing numerous waste management and coral reef conservation issues, the willingness to pay extra for sustainable hotel services was elicited. There were five discrete pricing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 61 publications
4
52
0
1
Order By: Relevance
“…Therefore, the environmental benefits of green logistics should be propagated to the CEP consumer via advertisements, social media, direct interactions, etc. This is because previous studies have shown that consumers' 'environmental knowledge' and 'preferences' play an important role in their willingness to pay more for green products [79]. Reusing, sharing boxes, and recycling, on the other hand, can be used to provide monetary incentives to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the environmental benefits of green logistics should be propagated to the CEP consumer via advertisements, social media, direct interactions, etc. This is because previous studies have shown that consumers' 'environmental knowledge' and 'preferences' play an important role in their willingness to pay more for green products [79]. Reusing, sharing boxes, and recycling, on the other hand, can be used to provide monetary incentives to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…The green certification corresponds to hotel guests’ demand and willingness to pay for them (Nelson et al , 2021). The green hotel certification program is significant to understanding the critical components of hotel environmental management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2016, approximately over 140 eco-labels focused on green hotel certifications. However, only 6.2% of the hotels were certified globally and 0.9% in Asia (Nelson et al , 2021). Although the green consumer segmentation has emerged since the 1960s (Zinkhan and Carlson, 1995), the value of green certification to consumers is still not well-understood across contexts, perhaps due to the low percentage of certified hotels (Gan and Nuli, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations